PHYSICOCHEMICAL AND THERMAL CHARACTERIZATION OF PRODUCTS FORMED DURING THE SLOW PYROLYSIS OF WOOD WASTE (Web of Teachers: Inderscience Research, 2026)
In this study, the yield and physicochemical properties of condensable products (wood vinegar and bio-oil), charcoal (biochar), and gas fractions formed during the slow pyrolysis of willow and poplar wood chips and board waste were investigated. In addition, the thermal stability of charcoal samples was evaluated. The results confirmed that the type of waste and particle size significantly affect product quality and energy characteristics.